Observation of parametric X-ray radiation excited by 50 GeV protons and identification of background radiation origin - Afonin, A.G.; Britvich, G.I.; Chesnokov, Yu.A.; Chirkov, P.N.; Durum, A.A.; Kostin, M.Yu.; Lutchev, A.V; Maisheev, V.A.; Yanovich, A.A.; Shchagin, A.V.; Truten’, V.I.; Ganenko, V.B.; et al. (Вопросы атомной науки и техники, 2013)
The experimental layout designed to study properties of focused parametric X-ray radiation generated by relativistic protons in a bent crystal and parametric X-ray radiation generated by relativistic ions and positrons at accelerator U70 is described. Preliminary results of measurements of spectra of characteristic and parametric X-rays observed at 50 GeV proton beam are shown and discussed. The origin of the background radiation that obstacles for detail research of the PXR properties at proton beam is identified. Moreover, the distribution of the ionization losses of relativistic charged particles in the X-ray detector similar to Landau distribution is measured and discussed. Описана експериментальна установка на виведеному пучку прискорювача У70, яка призначена для досліджень сфокусованого параметричного рентгенівського випромінювання (ПРВ) і ПРВ, збуджуваного релятивістськими іонами та ін. частинками. Наведено попередні результати вимірювань спектрів ПРВ і характеристичного рентгенівського випромінювань. Ідентифіковано походження спектрального фону, що перешкоджає дослідженням ПРВ на прискорювачі протонів. Виміряно і обговорюється розподіл іонізаційних втрат релятивістських заряджених частинок у рентгенівському детекторі, подібний розподілу Ландау. Описана экспериментальная установка на выведенном пучке ускорителя У70, которая предназначена для исследований сфокусированного параметрического рентгеновского излучения (ПРИ) и ПРИ, возбуждаемого релятивистскими ионами и др. частицами. Приведены предварительные результаты измерений спектров ПРИ и характеристического рентгеновского излучения. Идентифицировано происхождение спектрального фона, препятствующего исследованиям ПРИ на ускорителе протонов. Измерено и обсуждается распределение ионизационных потерь релятивистских заряженных частиц в рентгеновском детекторе, подобное распределению Ландау.